The impact of the COVID-19 pandemic in the clinical assistance to breast cancer patients
Purpose: We aimed to disclose the impact of the pandemic on breast cancer patients in a specialized breast cancer center (BCC). Methods: A total of 501 breast cancer patients with a first appointment in the BCC from April 1st, 2019 to March 31st, 2021 were divided into four consecutive periods of 6 months. Data from the homologous semesters was compared. Patients with an appointment in the BCC during the study period were eligible for the secondary aim of our study (BCC workload). Results: After the pandemic declaration (period 3), we found a decrease in the referral by screening programs (p = 0.002) and a reduction in the waiting time between the primary care referral and the first BCC appointment (p < 0.001). There were higher rates of palpable axillary nodes (p = 0.001), an increase in N stage 2 and 3 (p = 0.050), and a trend for primary endocrine therapy as the first treatment (p = 0.021) associated with higher rates of complete axillary node dissection (p = 0.030). In period 4, there were more outward diagnoses (p = 0.003) and a higher rate of surgery as the first treatment (p = 0.013). Conclusion: COVID-19 pandemic implied a more advanced nodal stage, which may be related to the delay in breast cancer screening.